أسئلة الرواية الجزائرية ( دوافع التاريخ وإرهاصات الواقع) - حجازي, محمد (Sciences humaines; Vol. 27 (2012): SCIENCES HUMAINES, 2014)
يتشكل الفعل الروائي وفق اتجاهات ثابتة ومتغيرة، حسب التنوع والانتماء والمعرفة. وتعددت الأسئلة وتنامت التجاوبات، وفق ذلك السرد المحرك للتصورات والمبدع لفعل الكتابة. وكان للرواية الجزائرية، موقع قدم في هذا التشابك والصراع الذي آل إلى المكاشفة عن مكنونات المجتمع ، وفق قواعد التساؤل والبحث عن المعرفة وخيوط الحقيقة. وعليه جاءت بعض النصوص السردية الروائية لتمثل هذا التناقض المجتمعي الصارخ، ولتكشف عن بعض التساؤلات التي تركتها مطروحة أيضا، بحجم علاقات المجتمع وأبجديات أنماط حياته وتساؤلاته العميقة والمختلفة. Formed the act in accordance with the directions novelist fixed and variable, according to the diversity and affiliation and knowledge. And there were many questions and resonances grown, according to the narrative engine of the perceptions and creative act of writing. The Algerian novel, presented in this site overlap and conflict which has fallen into the disclosure community Mknunat, according to the rules of the question and the search for knowledge and the truth leads. And it came some narrative fiction texts to represent this blatant contradiction community, and reveal some of the questions that also left on the table, the size of community relations and patterns alphabets deep his life and his questions and different.